2017
DOI: 10.1007/s11856-017-1471-5
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetry of complete and constant width bodies in general normed spaces and the Jung constant

Abstract: In this paper we state a one-to-one connection between the maximal ratio of the circumradius and the diameter of a body (the Jung constant) in an arbitrary Minkowski space and the maximal Minkowski asymmetry of the complete bodies within that space. This allows to generalize and unify recent results on complete bodies and to derive a necessary condition on the unit ball of the space, assuming a given body to be complete. Finally, we state several corollaries, e. g. concerning the Helly dimension or the Banach-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…, ε d+1 u d+1 }) = S, thus meaning that R(S) = 1, where R(•) stands for the circumradius (see [17,Proposition 2.1]). Hence, if D(S) denotes the diameter of S, then by Jung's theorem [24] (see also [3,Lemma 3;16,(3)]) we have that…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…, ε d+1 u d+1 }) = S, thus meaning that R(S) = 1, where R(•) stands for the circumradius (see [17,Proposition 2.1]). Hence, if D(S) denotes the diameter of S, then by Jung's theorem [24] (see also [3,Lemma 3;16,(3)]) we have that…”
Section: )mentioning
confidence: 99%
“…Hence there exist signs ε2,,εd+1 such that ρu1convfalse({ε2u2,,εd+1ud+1}false).In particular we have that 0conv(false{u1,ε2u2,,εd+1ud+1false})=S, thus meaning that R(S)=1, where R(·) stands for the circumradius (see [17, Proposition 2.1]). Hence, if D(S) denotes the diameter of S , then by Jung's theorem [24] (see also [3, Lemma 3; 16, (3)]) we have that D(S)R(S)2false(d+1false)d.Since the diameter of S is attained between two vertices of S , this means that either u1εiui2false(d+1false)dorεi1ui1εi2ui22false(d+1false)d,for...…”
Section: Selecting Two Vectorsmentioning
confidence: 99%
“…6] for the possibly most comprehensive overview), but amongst all, the one receiving most attention is the Minkowski asymmetry. In [5] it is shown how it naturally relates to complete and constant width sets in Minkowski spaces. Moreover, it has been repeatedly used to sharpen and strengthen geometric inequalities and related results, cf.…”
Section: Introductionmentioning
confidence: 99%
“…Denoting the n-dimensional Euclidean unit ball by B n 2 , Santaló (in case of n = 2) [25] and later Vrécica [29,Corollary 1] showed that r(K, B n 2 ) + R(K, B n 2 ) ≤ D(K, B n 2 ). The above inequality appears frequently in the literature (see e. g. [4] and [13]) and has been generalized to arbitrary Minkwoski spaces [11] (and even to general Banach spaces [11,22]), resulting in the concentricity inequality (the name pointing out that for the equality case it is necessary that every incenter is also a circumcenter -see [7,Lemma 2.4]): For all K, C ∈ K n with C (centrally) symmetric it holds (4) r(K, C) + R(K, C) ≤ D(K, C).…”
Section: Introductionmentioning
confidence: 99%
“…For the concentricity statement let us assume without loss of generality that C is Minkowski centered. It is shown in[7] that K is complete w. r. t. C − C implies that r(K, C − C)(C − C) ⊂ K − c ⊂ R(K, C − C)(C − C)for some Minkowski center c of K, thus K and C − C are Minkowski concentric. However, R(K,C) r(K,C) ≤ s(K)s(C) now implies by using Lemma 3.1 (e) again that r(K, C)C = 1 + 1 s(C) r(K, C − C)C ⊂ r(K, C − C)(C − C) ⊂ K − c ⊂ R(K, C − C)(C − C) ⊂ (1 + s(C))R(K, C − C)C = R(K, C)C, which shows K and C are Minkowski concentric.…”
mentioning
confidence: 99%